2024
DOI: 10.2298/psi220613009c
|View full text |Cite
|
Sign up to set email alerts
|

Problematic social media use, satisfaction with life, and levels of depressive symptoms in university students during the COVID-19 pandemic: Mediation role of social support

Abstract: The aim of the study was to investigate whether social support might mediate the relationship between problematic social media use (PSMU) and satisfaction with life, and depressive symptoms. The participants of this study consisted of 579 university students ranging in age between 17?38 years (M = 21.66, SD= 3.06). Participants completed the Multidimensional Perceived Social Support Questionnaire, the Depression, Anxiety, Stress Scale-21 (DASS-21), the Bergen Social Media Addiction Scale, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 110 publications
0
2
0
Order By: Relevance
“…A wealth of evidence shows that social support is a powerful resource that provides physical and psychological advantages for individuals facing challenging situations, and reduces psychological disturbances. 31 Effective support from spouses can relieve depression resulting from perceived stress among older adults. 32 The second pathway was "early parental conflict-marital relationships-parent-child relationships-current depression."…”
Section: Discussionmentioning
confidence: 99%
“…A wealth of evidence shows that social support is a powerful resource that provides physical and psychological advantages for individuals facing challenging situations, and reduces psychological disturbances. 31 Effective support from spouses can relieve depression resulting from perceived stress among older adults. 32 The second pathway was "early parental conflict-marital relationships-parent-child relationships-current depression."…”
Section: Discussionmentioning
confidence: 99%
“…16 Social support plays an important role in improving mental health. 17 , 18 Previous studies have shown a significant negative correlation between social support and parental stress levels, 19 which means people who receive more psychological or material support from family have better mental and physical health. 20 However, rarely lack of study has been discussed the relationship between social support and parents’ mental health literacy.…”
Section: Introductionmentioning
confidence: 99%